Strategi Komunikasi Pemasaran Politeknik LP3I Pekanbaru Dalam Meningkatkan Jumlah Mahasiswa Baru - Roshiful Qolbi; Nurul Huda; Yetnimar; Hikmah Sri Ujari (CV. ITTC INDONESIA, 2025)
A marketing communication strategy is an approach used by a company to interact with its target market. Marketing communication strategies aim to create brand awareness, influence consumer behavior, and build strong relationships with customers. Marketing can be carried out using various methods and means. In today's modern era, many media can be used to run a business and implement various promotions such as advertising and event packaging, direct selling, and the use of public relations strategies. LP3I Pekanbaru Polytechnic is one of the lines of Higher Education. LP3I Pekanbaru Polytechnic is a Vocational Campus with a learning system that is 70% practical and 30% theoretical. In addition, LP3I Pekanbaru Polytechnic has also linked you to match with the world of work. The research outlined in this study aims to determine the preparation and planning of promotional programs at LP3I Pekanbaru Polytechnic. The research method used is a qualitative research method with a case study approach that occurs in the field and analyzes the data obtained in the field. Data were collected using library methods, observation, and interviews. After analyzing and discussing the problem, the author concluded that the promotional activities carried out by the LP3I Pekanbaru Polytechnic began with thorough planning and preparation by the team, followed by presentations to schools in Pekanbaru and outside the region, and disseminating information through social media such as Facebook, Instagram, and YouTube.